Examining the role of environmental corporate social responsibility in building green corporate image and green competitive advantage - S. M. Shafiul Alam; K. M. Zahidul Islam (International Journal of Corporate Social Responsibility (JCSR), 2021)
Green concern is making a profound impact on building green competitive advantage (GCA) across the globe. Apparel sector of Bangladesh is at crossroads regarding sustainability of firms. Green initiatives are thus required for ensuring the survival of apparel sector. The current study attempts to examine the interplay among environmental corporate social responsibility (ECSR) dimensions, green corporate image (GCI), and green competitive advantage of firms. To address the research topic, structural equation modeling approach has been adopted. Based on prior research findings, five hypotheses have been devised and finally evaluated by collecting data from 53 apparel firms enlisted with Dhaka Stock Exchange, Bangladesh. The study findings reveal that the ECSR dimensions have critical role to play over building GCI and GCA at the firm level. The study attempted to integrate ECSR, GCI, and GCA and contributes to the holistic understanding of the green anxieties of the business world. Understanding the critical role of ECSR, this study calls for proactive managerial actions regarding organizational sustainability.
Keywords: 650; Environmental corporate social responsibility dimensions; Green corporate image; Green corporateadvantage; Structural equation modeling